2002
DOI: 10.1046/j.1365-2923.2002.01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning in groups: Teamshaping in the teaching of medical psychology

Abstract: The model is recommended for teaching medical students because it not only extends traditional teaching towards small group learning but adds a competency in teamwork. It introduces students to a better working style and gives them an additional perspective for use in their future profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This quote, commonly attributed to Henry Ford, nicely illustrates the emphasis that has been placed on teamwork within many areas of society, including business, politics, and education. The health sciences are not an exception to this rule, as evidenced by both the inclusion of a collaborator role within the CanMEDs 2000 report published by the Royal College of Physicians and Surgeons of Canada, 1 and a pair of articles included in this issue that describe attempts to develop intra‐ and interprofessional team‐building opportunities for students 2 , 3 . Ford's quote, however, also illustrates one of the problems that this emphasis on teamwork has created – the tendency to treat teamwork as a goal in and of itself.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This quote, commonly attributed to Henry Ford, nicely illustrates the emphasis that has been placed on teamwork within many areas of society, including business, politics, and education. The health sciences are not an exception to this rule, as evidenced by both the inclusion of a collaborator role within the CanMEDs 2000 report published by the Royal College of Physicians and Surgeons of Canada, 1 and a pair of articles included in this issue that describe attempts to develop intra‐ and interprofessional team‐building opportunities for students 2 , 3 . Ford's quote, however, also illustrates one of the problems that this emphasis on teamwork has created – the tendency to treat teamwork as a goal in and of itself.…”
mentioning
confidence: 99%
“…Furthermore, the deleterious effects of teamwork are not limited to those situations in which the teams are composed of individuals from varying disciplines. Also in this issue, Kropiunigg, Pucher, and Weckenmann report using the Group Climate Questionnaire in an attempt to evaluate the effectiveness of Teamshaping (defined as small group learning in which attention is turned to the personal experiences of the group) compared to `traditional' teaching of medical psychology as a way to induce (in third year medical students) the ability to work in teams 2 . The reliability and validity of this questionnaire were not reported, but it was intended to be a measure of the relationship among group members along three dimensions: Commitment, conflict, and avoidance/dependence.…”
mentioning
confidence: 99%
“…Accreditation and supervisory bodies in medical education also advocate building the teamwork capabilities of medical students (AMC, 2012;Frank, Snell, & Sherbino, 2014;General Medical Council, 2015;Liaison Committee on Medical Education, 2011). Teamwork training can be integrated within a small-group instructional approach (Kropiunigg, 2002;Kropiunigg, Pucher, & Weckenmann, 2002;Sobral, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A majority of students ranked the role of the faculty member as least important in the group process of small-group learning [ 6 ], and several researchers have found that students prefer peer-led groups [ 6 - 10 , 20 - 22 ]. Student behavior and group functioning appears to be influenced by their perception of the learning situation [ 23 ], which suggests that students might do better in small group situations led by peers. Group functioning, in turn, is correlated with academic performance [ 19 ].…”
Section: Introductionmentioning
confidence: 99%